Improving Students Vocabulary By Study Club Method - Ramadhani, Fauzia; Aldini, Rizka; Salma, Zahara; N, Nashuha; Siregar, Rahmat; I, Ihsanatantri (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Research aims to explain how to improve mastery of English vocabulary using group learning methods or cooperative learning methods. Data collection was carried out using the Internet Searching method , namely searching for data through internet media to obtain information based on references, journals and articles. And the author carries out documentation techniques by obtaining strong evidence through books that contain information and to support information about Improving Students Vocabulary By Study Club Method and Research This is also a literature review research (Library Research) by reviewing theses and journals related to English language learning in elementary schools. The results show that the approach to learning English at the play group level up to elementary school using a cooperative learning model is empirically proven to be able to improve the learning process, learning achievement and student learning completion. Keywords: English learning, elementary school, cooperative learning